Fade to Black? Exploring Policy Enactment and Termination Through the Rise and Fall of State Tax Incentives for the Motion Picture Industry. (January 2017) - Thom, Michael; An, Brian
Policy termination has received less scholarly attention than policy diffusion, and empirical state-level studies that examine the rise and fall of the same policy are mostly absent from the literature. This study assesses the factors that led more than 45 states to enact and some to later repeal Motion Picture Incentive programs, a collection of tax incentives aimed at facilitating job creation and economic diversification. We find program enactments were driven by rising unemployment and national but not bordering state imitation. Falling unemployment and national trends drove subsequent terminations, but in many states, their impact was overwhelmed by the influence of incentive spending, which greatly reduced termination likelihood. These results not only shed light on policy enactments and terminations in general, but also inform scholarship on state tax incentives and the role of competitive factors in their creation and repeal—or lack thereof.